The abortion law: A reform / Florence Toh Huat Neo - Florence Toh, Huat Neo (1975)
Today 58% ot the world's population live in countries with leplized or liberalized abortion (legalized abortion meaning abortion on demand and liberalized abortion meaning abortion is permitted only under certain conditions). Five of the six most populous countries in the world - China, India, United States, Japan and Soviet Union - permit abortion on demand in early pregnancy. That abortion is becoming Increasingly popular is an undeniable fact. Even in those countries where abortion is not permitted save where the lite of the mother is in danger, illegal abortions thrive.